Principles of strategic data science creating value from data, big and small - Prevos, Peter (Packt Publishing Ltd., 2019)
Principles of Strategic Data Science describes a framework that creates value from data to help organizations meet their objectives. With this book, you'll bridge the gap between mathematics and computer science and also gain insight into the workings of the entire data science pipeline.